ONAC066, A Stress-Responsive NAC Transcription Activator, Positively Contributes to Rice Immunity Against Magnaprothe oryzae Through Modulating Expression of OsWRKY62 and Three Cytochrome P450 Genes - Yuan, Xi; Wang, Hui; Bi, Yan; Yan, Yuqing; Gao, Yizhou; Xiong, Xiaohui; Wang, Jiajing; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2021)
NAC transcriptional factors constitute a large family in rice and some of them have been demonstrated to play crucial roles in rice immunity. The present study investigated the function and mechanism of ONAC066 in rice immunity. ONAC066 shows transcription activator activity that depends on its C-terminal region in rice cells. ONAC066-OE plants exhibited enhanced resistance while ONAC066-Ri and onac066-1 plants showed attenuated resistance to Magnaporthe oryzae. A total of 81 genes were found to be up-regulated in ONAC066-OE plants, and 26 of them were predicted to be induced by M. oryzae. Four OsWRKY genes, including OsWRKY45 and OsWRKY62, were up-regulated in ONAC066-OE plants but down-regulated in ONAC066-Ri plants. ONAC066 bound to NAC core-binding site in OsWRKY62 promoter and activated OsWRKY62 expression, indicating that OsWRKY62 is a ONAC066 target. A set of cytochrome P450 genes were found to be co-expressed with ONAC066 and 5 of them were up-regulated in ONAC066-OE plants but down-regulated in ONAC066-Ri plants. ONAC066 bound to promoters of cytochrome P450 genes LOC_Os02g30110, LOC_Os06g37300 and LOC_Os02g36150 and activated their transcription, indicating that these three cytochrome P450 genes are ONAC066 targets. These results suggest that ONAC066, as a transcription activator, positively contributes to rice immunity through modulating the expression of OsWRKY62 and a set of cytochrome P450 genes to activate defense response.